P‐1.13: Influence of the Source/Drain Material on Oxide Semiconductor Thin Film Transistors. (28th November 2018) - Liang, Yi; Han, Dedong; Yu, Wen; Dong, Junchen; Li, Huijin; Luo, Zhen; Yi, Zhuang; Zhang, Shengdong; Zhang, Xing; Wang, Yi
Abstract : With the progress of technology, the display devices are also developing in the direction of lightweight, inexpensive, diversification. In order to drive the light emitting devices, people need to research on active‐matrix thin film transistors (TFTs) .In this paper, indium gallium zinc oxide (IGZO) is chosen as the active layer material, and we use four different types of source/drain materials including indium‐tin‐oxide (ITO), Al, Al‐doped zinc oxide (AZO) and Ga‐doped zinc oxide (GZO) to explore the influence of different source/drain materials on the characteristics of oxide semiconductor thin film transistors (TFT). The results show that TFTs with AZO as source/drain electrodes exhibit good characteristics. After 200°C annealing, the output characteristic of TFT with AZO as source/drain electrodes becomes better and its source/drain series resistance is low. From this study, AZO can be considered as a hopeful source/drain material which would be utilized in the future displays technology.